Ultrasound-Mediated Non-Specific Splenic Immunopotentiation to Elicit Broad-Spectrum Anti-Neoplastic Effects - Dong W; Wang G; Li S; Wang Q; Li W; Liu H; Liang Y; Zhou Z; He X; Guo W; Yuan J; Chai Y; et al. (ImmunoTargets and Therapy)
Wei Dong,1– 4 Guihu Wang,1– 3 Senyang Li,1– 3 Qian Wang,1– 3 Wenjuan Li,3 Heyuan Liu,3 Yingxue Liang,3 Zhe Zhou,1,2,4 Xinrui He,2,4 Wenlei Guo,2,4 Jianing Yuan,2,4 Yichao Chai,1,4 Jing Geng,1– 3 Zongfang Li1– 4 1National and Local Joint Engineering Research Center of Biodiagnostics and Biotherapy, the Second Affiliated Hospital, Xi’an Jiaotong University, Xi’an, People’s Republic of China; 2Shaanxi Provincial Clinical Medical Research Center for Liver and Spleen Diseases, CHESS-Shaanxi Consortium, the Second Affiliated Hospital, Xi’an Jiaotong University, Xi’an, People’s Republic of China; 3Center for Tumor and Immunology, the Precision Medical Institute, Xi’an Jiaotong University, Xi’an, People’s Republic of China; 4Department of Geriatric General Surgery, the Second Affiliated Hospital, Xi’an Jiaotong University, Xi’an, People’s Republic of ChinaCorrespondence:Zongfang Li; Jing Geng, Email lzf2568@mail.xjtu.edu.cn; jgeng18@xjtu.edu.cnBackground: Splenic immunomodulation triggered by ultrasound shows a significant anti-inflammatory effect against various inflammatory diseases, whose mechanism is mainly attributable to the activation of cholinergic anti-inflammatory pathway (CAP). However, the potential role and underlying mechanism of splenic ultrasound stimulation in cancer management have been rarely reported and superficially defined.Methods: Following optimization of ultrasonic parameters, this study evaluated the anti-tumor efficacy of splenic sonication across multiple tumor models (eg, orthotopic H22 hepatocellular carcinoma (HCC), orthotopic Hepa1-6 HCC, and subcutaneous 4T1 breast cancer), and applied flow cytometry to quantify dynamic alterations in immune cell populations. Furthermore, in orthotopic H22 HCC models, this study employed fluorescence-activated cell sorting, RNA sequencing, splenic nerve blockade via absolute ethanol ablation, and in vitro Ca²⁺ flux assays to delineate the mechanisms underlying ultrasound-mediated splenic anti-tumor immunity.Results: This study first assessed the therapeutic effect of focused ultrasound precisely targeting the spleen (FUS sti. spleen) on various tumors at specific ultrasonic doses. It fully demonstrated that FUS directly stimulated splenic immune cell proliferation and activation (especially NK and CD8 T cells) rather than CAP excitation to modulate splenic immune function. Particularly, NK cells are much more indispensable and important in responding to FUS stimulation for cancer suppression than CD8 T cells. RNA sequencing of NK and CD8 T cells, as well as in vitro experiments revealed that FUS firstly regulated calcium-related signaling pathways to further modulate others, such as PI3K-AKT, Rap1, and Hippo pathways to promote immune cell proliferation, migration and activation to suppress cancer cell deterioration. Particularly, FUS sti. spleen and FUS intervention on the tumor synergistically induced the best tumor suppression than each of the two taken individually.Conclusion: FUS sti. spleen facilitated immunocyte proliferation and activation through altering calcium-dependent signaling rather than CAP excitation to modulate anti-tumor immunity, indicating substantial clinical translation potential. Keywords: focused ultrasound, spleen, FUS sti. spleen, splenic immunomodulation, tumor suppression